Investigation on welding residual stress and vibration characteristics of ring-stiffened cylindrical shell - Jiangchao WANG; Xiangfei CHEN; Yexing NIU; Shizhong DU; Chaonan SHEN (Zhongguo Jianchuan Yanjiu, 2023)
ObjectiveThis study investigates complex welding residual stress and its effect on the vibration characteristics of a ring-stiffened cylindrical shell.MethodsFusion welding with carbon dioxide as the shield gas is employed to finish the welding of a ring-stiffened cylindrical shell. The non-destructive X-ray diffraction (XRD) approach is used to measure the longitudinal residual stress of critical regions after welding and annealing heat treatment. Effective thermal elastic-plastic finite element (FE) computation is then used to examine the temperature and welding residual stress during welding, as well as considering the influence of the moving body heat source and fixed heat source on welding computation. Under the state of freedom, the vibration characteristics of the examined ring-stiffened cylindrical shell after welding and annealing heat treatment are measured, and the vibration modes and corresponding natural frequency are both predicted with FE analysis.ResultsBased on experimental measurement, thermal elastic-plastic FE computation measurement during welding and structural vibration is carried out, and the residual stress and vibration characteristics of the ring-stiffened cylindrical shell after welding and annealing heat treatment are obtained.ConclusionsA fixed heat source can effectively predict the thermal and mechanical response during the welding of a ring-stiffened cylindrical shell, and the predicted welding residual stress shows good agreement with the measurements. Annealing heat treatment can significantly reduce welding residual stress and lower its influence on the vibration characteristics of a ring-stiffened cylindrical shell.